Proinflammatory cytokines interleukin-18 and interleukin-6 mediate anorexia induction by trichothecene deoxynivalenol and its congeners - Zhou, Chuang; Qin, Zihui; Zhang, Huayue; Xiao, Huiping; Zhang, Hua (Frontiers in Veterinary Science, 2024)
As the common foodborne mycotoxins with the highest pollution rate, deoxynivalenol (DON, also named “vomitoxin”) can harm the health of humans and animals by causing anorectic response. It has four congeners: 3-acetyldeoxynivalenol (3-ADON), 15-acetyldeoxynivalenol (15-ADON), nivalenol (NIV), and fusarenon X (FX). These five mycotoxins have been associated with the detrimental effect on food intake. However, its underlying mechanism of anorexia remains unclear. The goal of this research was to compare the anorectic responses to these five mycotoxins and relate these effects to proinflammatory cytokines interleukin-18 (IL-18) and interleukin-6 (IL-6) following intraperitoneal (IP) and oral exposure to a common dose at 2.5 mg/kg BW in mice. Plasma IL-18 and IL-6 were elevated within 1–2 h and returned to basal levels at 6 h after exposure to DON, 3-ADON and 15-ADON. FX promoted IL-18 expression at 6 h. Whereas, FX only promoted IL-6 at 6 h. When NIV was injected intraperitoneally, IL-18 started to rise at 1 h and peaked at 6 h. Whereas, NIV only promoted IL-18 at 2 h following oral exposure. IP exposure to NIV induced an increase in IL-6 that occurred only at 2 h. No effect on IL-6 when exposed orally to NIV. In conclusion, the data indicate that IL-18 and IL-6 play critical roles in anorectic response induced by DON and its four congeners 3-ADON, 15-ADON, NIV, FX.